UJi Formulasi Ransum Makanan Sapi yang Berasal dari Limbah Pertanian Terhadap Penampilan Ternak Sapi - Dewi Ratna Nurhayati, Siswadi & (Eksplorasi, 2009)
Abstract Traditional breeding cow has varied productivity. This is because the effects of environtment. Among them is the difference of feed condition. Generally, traditional cattle breeders only give greens as main diet.Â The use of greens such as paddy straws and grass as cow feeding is an abundant and potential source and energy. However, because of its low nutrient content and high bycomponents, the use of paddy straw needs to be effective. One of the alternatives is by mixing concentrate so that a balance diet can be achieved to enhance the cattle productivity.Â Concentrate as a stimulant diet contains high nutrient. Because the high price of concentrate , it is suggested that is should be replaced by other effective and available concentrate such as cow concentrate. The research was conducted in Desa Mranggen, Kecamatan Polokarto, Kabupaten SUkoharjo which was selected from SIBERMAS program from January until September 2008. Treatments consist of A: fermented paddy straw without the adding of Urea Molasses Block (UMB), B: Fermented paddy straw with Urea Molsses Block. Each treatment consists of 5 time repetition â€“ with test analysis. Parameter that was investigated in this research was the increase of daily weight. It was gathered from the last weight minus the first weight divided by length of breeding. Diet conversion counted by the amount of consumption feeding (gram/cattle/day) with increased weight (gram/cattle/day), feed cost per gain counted by the total amount of feeding cost divided by average increase weight. From this research, it can be concluded that by using fermented straw added by urea molasses block of 3.5 ky/day give significant performance on cow growth. Keywords : diet, urea molasses block, formulation